Peritoneal dialysis in childhood acute kidney injury: experience in Southwest Nigeria (2012)
Background: The choices for renal replacement therapy (RRT) in childhood acute kidney injury (AKI) are lim¬ited in low-resource settings. Peritoneal dialysis (PD) appears to be the most practical modality for RRT in young children with AKI in such settings. Data from sub-Saharan Africa on the use of PD in childhood AKI are few. Methods: We performed a retrospective study of chil¬dren who underwent PD for AKI at a tertiary-care hospital in southwest Nigeria from February 2004 to March 2011 (85 months). Results: The study included 27 children (55.6% female). Mean age was 3.1 ± 2.6years, with the youngest being 7 days, and the oldest, 9 years. The causes of AKI were in¬travascular hemolysis (n = 11), septicemia (n = 8), acute glomerulonephritis (n = 3), gastroenteritis (n = 3), and hemolytic uremic syndrome (n = 2). Peritoneal dialysis was performed manually using percutaneous or adapted catheters. Duration of PD ranged from 6 hours to 12 days (mean: 5.0 ± 3.3 days). The main complications were peri¬tonitis (n = 10), pericatheter leakage (n = 9), and catheter outflow obstruction (n = 5). Of the 27 patients, 19 (70%) survived till discharge. Conclusions: In low-resource settings, PD can be suc¬cessfully performed for the management of childhood AKI. In our hospital, the use of adapted catheters may have contributed to the high complication rates. Peritoneal di¬alysis should be promoted for the management of childhood AKI in low-resource settings, and access to percutaneous or Tenckhoff catheters, dialysis fluid, and automated PD should be increased.